Enhancing Students' Critical Thinking Through Active Teaching Methods: An Experimental Approach Integrating Inclusive Leadership in Higher Education - Nam, Ong Van (Journal of Posthumanism, 2024)
Based on survey data collected from 539 undergraduate students at public and private universities in Vietnam, this study applies foundational theories and previous research to analyze and evaluate the impact of active teaching methods and inclusive leadership on students' critical thinking and academic performance. By employing advanced data analysis techniques such as Cronbach’s Alpha reliability testing, Exploratory Factor Analysis (EFA), and Partial Least Squares Structural Equation Modeling (PLS-SEM) using SPSS and SmartPLS software, the study presents several key findings. Specifically: (1) Active teaching methods have a significant and positive impact on enhancing students' critical thinking and academic performance; (2) Inclusive leadership plays a crucial mediating role in strengthening the relationship between active teaching methods and both critical thinking and academic performance; (3) Critical thinking has a strong and positive influence on students' academic performance. These findings highlight the importance of integrating active teaching methods and inclusive leadership in higher education to foster students' cognitive development and learning outcomes. The coordinated application of these elements not only contributes to improving educational quality but also lays the foundation for building an inclusive, equitable, and sustainable learning environment in the context of ongoing educational innovation.